Characterization and Expression Analysis of ERF Genes in Fragaria vesca Suggest Different Divergences of Tandem ERF Duplicates - Wang, Xiaojing; Lin, Shanshan; Liu, Decai; Wang, Quanzhi; McAvoy, Richard; Ding, Jing; Li, Yi (Frontiers in Genetics, 2019)
Ethylene responsive factors (ERFs) play important roles in plant growth and development, and responses to abiotic stresses. However, little information was available about the ERF genes in woodland strawberry (Fragaria vesca), a genetic model plant for the Fragaria genus and Rosaceae family. In this study, 91 FveERF genes were identified, including 35 arrayed in tandem, indicating that tandem duplication is a major mechanism for the expansion of the FveERF family. According to their phylogenetic relationships with AtERFs from Arabidopsis thaliana, the tandem FveERF genes could be grouped into ancestral and lineage-specific tandem ones. The ancestral tandem FveERFs are likely derived from tandem duplications that occurred in the common ancestor of F. vesca and A. thaliana, whereas the lineage-specific ones are specifically present in the F. vesca lineage. The lineage-specific tandem FveERF duplicates are more conserved than the ancestral ones in sequence and structure. However, their expression in flowers and fruits are similarly diversified, indicating that tandem FveERFs have diverged rapidly after duplication in this respect. The lineage-specific tandem FveERFs display same response patterns with only one exception under drought or cold, whereas the ancestral tandem ones are largely differentially expressed, suggesting that divergence of tandem FveERF expression under stress may have occurred later than in reproductive development. Our results provide evidence that the retention of tandem FveERF duplicates soon after their duplication may be related to their divergence in the regulation of reproductive development. In contrast, their further divergence in expression pattern likely contributes to plant response to abiotic stress.